2010
DOI: 10.1159/000275064
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of Ascending Colon Associated with Sarcoid Reaction in Regional Lymph Nodes

Abstract: Lymph node swelling in the setting of malignancy generally suggests metastasis of the primary tumor. A granulomatous reaction, i.e. sarcoid reaction, occurring within the lymph nodes draining carcinomas is a well-known but uncommon occurrence. The phenomenon is especially rarely seen in colon carcinoma. We herein report a rare case of a 56-year-old Japanese male with adenocarcinoma of the ascending colon associated with sarcoid reaction in the regional lymph nodes. A typical ileocecal resection and lymph node … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…We have only found two cases, one corresponding to a poorly differentiated colonic adenocarcinoma in the ascending colon and the second in the sigmoid colon (5,6).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…We have only found two cases, one corresponding to a poorly differentiated colonic adenocarcinoma in the ascending colon and the second in the sigmoid colon (5,6).…”
Section: Discussionmentioning
confidence: 82%
“…The last possible mechanism is a simple tissue reaction to a tumor embolism in the lymphatic system or capillaries, or by the mere presence of tumor cells (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,8,9,13-15,21,23,33,45-56 , 5,7,10-12,16-20,22,24,25,27-32,34-44,59 Most often, these reactions are observed in lymph nodes draining the malignancy but can also occur in distant organs or the tumor-affected organ itself. [5][6][7][10][11][12][16][17][18][19][20]22,24,25,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]46,47,59 The mechanism for sarcoidlike reactions remains unknown. 46 Some authors have suggested a T-cell-mediated host response to soluble tumor antigens and others a reaction to tumor cell metabolites.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] In terms of their pathophysiology, it has been speculated that such granulomatous responses could represent hypersensitivity reactions to certain tumor antigens or constitute innate immune reactions to tumor cell necrosis. 12,15 Ipilimumab, by unleashing T-cell-mediated immune responses, facilitates local and systemic production of cytokines.…”
Section: Discussionmentioning
confidence: 99%